ISO 9001: International Standards and their impact on achieving competitive advantage /An Applied at the private colleges in Iraq - عبد اللطيف, فائز غازي (Journal of Economics and Administrative Sciences, 2018)
The results of the analysis showed that there is a correlation between ISO 9001    and the competitive advantage, which shows that the implementation of ISO 9001 in the private colleges achieves a competitive advantage through its ability to employ the entrance of quality systems management according to ISO 9001, By focusing on improving the quality of its educational services in accordance with a clear and understandable policy for all and its ability to meet the expectations, expectations and wishes of students and beneficiaries, which leads to lower costs of operations compared to other colleges and achieve a higher level of reliability and quality and value of services provided and rapid response and adaptation to environmental changes and commitment to time and speed in completion Its services, development and continuous improvement and support for all levels of creativity. The most important recommendations must be convinced by the administration of the civil colleges and their councils by applying the international standard ISO 9001: 2008 so that the LED Support and support for the necessary changes that may occur.